Bioinformatic characterisation of genes associated with coenzyme A biosynthesis in mycoplasmas and expression and isolation of dephospho-coenzyme A kinase from Mycoplasma sp. Ms02 - Ras, Tertius Alwyn (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.